A Framework for Equitable Partnerships to Promote Cancer Prevention and Control in Rural Settings. Issue 2 (16th February 2022) - Ko, Linda K; Scarinci, Isabel C; Bouchard, Elizabeth G; Drake, Bettina F; Rodriguez, Elisa M; Chen, Moon S; Kepka, Deanna; Kruse-Diehr, Aaron J; Befort, Christie; Shannon, Jackilen; Farris, Paige E; Trentham-Dietz, Amy; et al.
Abstract: Rural populations continue to experience persistent cancer disparities compared with urban populations particularly in cancers that can be prevented or detected early through screening and vaccination. Although the National Cancer Institute and the larger cancer research community have identified rural community partnerships as the foundation for reducing the disparities, we have identified limited application of community-based participatory research in cancer prevention and control research. Guided by the Community-Based Participatory Research Conceptual Model and our collective experience, we provide a framework for a community–cancer center partnership that focuses on promoting health equity. In this commentary, we articulate that the partnership process must foster capacity for communities and cancer centers, strive for rural representation in clinical trials and biobanking, build a pipeline for dissemination and implementation research, and create a bidirectional flow of knowledge between communities and academic institutions. Authentic partnerships with rural communities should be the ultimate goal of cancer centers, and the process described in this commentary can serve as an initial platform to build capacity and continue to strive toward that goal.